DESAIN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATERI KOLOID DI SEKOLAH MENENGAH KEJURUAN NEGERI PERTANIAN TERPADU PROVINSI RIAU - Yudha Febriyanto; Lisa Utami; Zona Octarya (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2020)
This research was instigated by unavailability of independent learning resource in the form of Android based instructional media at the school. This research aimed at knowing the validity and practicality levels of Android based instructional media that was valid and practical on Colloid lesson. It was Research and Development (R&D) with 4D development model. The subjects of this research were material and media experts, Chemistry subject teachers, 10 students at the eleventh grade of APHP 1. The object was Android based instructional media on Colloid lesson. The collected data were primary—the data were obtained directly from a questionnaire. Instruments of collecting the data were the questionnaires of validity test, practicality test, and student response. The obtained data then were analyzed by using qualitative and quantitative descriptive analysis techniques. The developed instructional media was tested, its validity level was 95.35% and it was on very valid category, its practicality level was 86.36% and it was on very practical category, and student response was 92.14% and it was on very practical category. Based on these results, it could be identified that Android based instructional media was appropriate and practical to be a learning resource at a school.